2016
DOI: 10.18632/oncotarget.13510
|View full text |Cite
|
Sign up to set email alerts
|

Accumulated promoter methylation as a potential biomarker for esophageal cancer

Abstract: We performed a two-stage molecular epidemiological study to explore DNA methylation profiles for potential biomarkers of esophageal squamous cell carcinoma (ESCC) in a Chinese population. Infinium Methylation 450K BeadChip was used to identify genes with differentially methylated CpG sites. Sixteen candidate genes were validated by sequencing 1160 CpG sites in their promoter regions using the Illumina MiSeq platform. When excluding sites with negative changes, 10 genes (BNIP3, BRCA1, CCND1, CDKN2A, HTATIP2, IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…The same authors proved that the tumor suppressor miR-101 could reverse the PRDM16 hypomethylation status thus suppressing its expression through direct epigenetic regulation, finally leading to mitochondrial disruption and apoptosis [257]. Similarly, PRDM16 hypomethylation was also described in glioblastoma [258] whereas a study suggested that PRDM16 hypermethylation level might be used as a potential biomarker for the diagnosis of esophageal cancer [259]. Altogether, these findings indicate that PRDM16 methylation status, both hypermethylation and hypomethylation, is often affected in distinct cancers, where this gene can play alternatively a role as an oncogene or as a tumor suppressor gene.…”
Section: Prdm16mentioning
confidence: 95%
“…The same authors proved that the tumor suppressor miR-101 could reverse the PRDM16 hypomethylation status thus suppressing its expression through direct epigenetic regulation, finally leading to mitochondrial disruption and apoptosis [257]. Similarly, PRDM16 hypomethylation was also described in glioblastoma [258] whereas a study suggested that PRDM16 hypermethylation level might be used as a potential biomarker for the diagnosis of esophageal cancer [259]. Altogether, these findings indicate that PRDM16 methylation status, both hypermethylation and hypomethylation, is often affected in distinct cancers, where this gene can play alternatively a role as an oncogene or as a tumor suppressor gene.…”
Section: Prdm16mentioning
confidence: 95%
“…Underlying genetic alterations, including promoter methylation, copy number variations (CNVs) and chromosomal instability (CIN), have been reported to regulate histone modification-associated gene expression. For instance, low PRDM16 expression levels in non-small cell lung cancer and esophageal cancer were reported to be correlated with its promoter methylation (49,50). A high frequency of CNVs at 1p36.32 harboring the PRDM16 gene was observed in GC, suggesting that changes in gene CNVs also have vital roles in regulating gene expression (51).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Subsequently, 18 studies were identified for full-text reading. After reading the full-text of the 18 studies, 10 studies were excluded for the following reasons: two were not about cancer [24,25], five did not refer to circulating PTX3 [26][27][28][29][30], two articles did not report the diagnostic performance of circulating PTX3 in cancer detection [31,32], one paper did not present sufficient data [33]. Finally, eight papers involving nine studies were included in this meta-analysis [12][13][14][15][16][34][35][36]].…”
Section: Study Selectionmentioning
confidence: 99%